The role of ultrasound in the diagnosis of vesicoureteral reflux disease - Mert Doğan, Güleç; Sığırcı, Ahmet; Elmas, Ahmet Taner; Tabel, Yilmaz (Journal of Surgery and Medicine, 2022)
Background/Aim: The gold standard in the diagnosis of VUR (vesicoureteral reflux) is voiding cystouretrography (VCUG), but it is an invasive test with risk of radiation. The aim of the study was to determine the sensitivity, specificity, positive and negative predictive values (PPV and NPV, respectively) of ultrasound (US) in the diagnosis of VUR. Methods: 760 kidneys of 380 patients were examined in this cohort study. The patients were grouped by three age groups; 0-2, 3-5 and 6-17 years old. US reports included the data of anteroposterior renal pelvic diameter (APRPD), kidney parenchyma, kidney size, and the size of ureters. For all age groups, the sensitivity, specificity, PPV and NPV were evaluated separately in two circumstances; APRPD is accepted pathologic when >5 mm and >10 mm. Results: A correlation was found between VCUG and US results in all age groups (P<0.001). When pathologic APRPD was accepted as >5 mm, sensitivity, specifity and NPV of US were 86.99%, 60.26% and 88.13% respectively, regardless of age. In contrast, when pathologic APRPD was >10 mm, sensitivity, specifity and NPV were 79.45%, 79.91% and 71.17%, respectively. Sensitivity and NPV of US were found highest in group of 0-2 age. Conclusion: If US are performed by radiologists experienced in the pediatric urinary system US and if it includes other parameters with APRPD, it will guide for VCUG in the diagnosis of VUR. Thus, radiation exposure can be minimalized in clinical practice.